2023
DOI: 10.3390/molecules28031131
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Analysis of Essential Oil Composition of Artemisia annua L. Collected from Different Locations in Korea

Abstract: Artemisia annua L. is distributed throughout the world and it is an important medicinal plant in Korea to treat various human diseases. Recently, A. annua has also been considered to be an effective ethnobotanical drug against COVID-19. A. annua contains an appreciable amount of essential oil with different biological properties. However, the composition of essential oils in aromatic plants can be varied depending on several factors, including geographic, genetic, ecological, etc. Hence, the present study aime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…The sesquiterpene lactone artemisinin derives from amorpha-4,11-diene through the pathway artemisinic alcohol → artemisinic aldehyde → dihydroartemisinic aldehyde dihydroartemisinate → dihydroartemisinic acid hydroperoxide → artemisinin), while arteannuin b is derived from artemisinic aldehyde and artemisinate [47,48]. Our research confirmed the previous findings that camphor is among the most abundant compound in A. annua extracts [3,4]. Other study conducted by Dobreva et al [49] found 28 different compounds in the subcritical extract of A. annua detected by GC-MS analysis of the supercritical extract obtained with 1,1,1,2-tetrafluoroethane and the major ones were artemisia ketone (26.2%), camphor (10.7%), and eucalyptol (9.1%) followed by artheanin B (3.7%) and arteannuic acid (3.7%).…”
Section: Supercritical Co 2 Extraction (Sco 2 E)supporting
confidence: 90%
See 2 more Smart Citations
“…The sesquiterpene lactone artemisinin derives from amorpha-4,11-diene through the pathway artemisinic alcohol → artemisinic aldehyde → dihydroartemisinic aldehyde dihydroartemisinate → dihydroartemisinic acid hydroperoxide → artemisinin), while arteannuin b is derived from artemisinic aldehyde and artemisinate [47,48]. Our research confirmed the previous findings that camphor is among the most abundant compound in A. annua extracts [3,4]. Other study conducted by Dobreva et al [49] found 28 different compounds in the subcritical extract of A. annua detected by GC-MS analysis of the supercritical extract obtained with 1,1,1,2-tetrafluoroethane and the major ones were artemisia ketone (26.2%), camphor (10.7%), and eucalyptol (9.1%) followed by artheanin B (3.7%) and arteannuic acid (3.7%).…”
Section: Supercritical Co 2 Extraction (Sco 2 E)supporting
confidence: 90%
“…Recently, there are more and more scientific investigations on the health impact of plant bioactive compounds. Increasing research interest also concerns Artemisia annua L. (commonly known as sweet wormwood, sweet annie or qinghao), which is an annual plant belonging to the Asteraceae family and grows in spring across the world [1][2][3][4]. Sweet wormwood plant has been used in traditional Chinese medicine for over 2000 years as a remedy for many disorders such as fever or inflammation [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the remarkable fluctuations in the EO yield and variability in its chemical composition, even among the same specimens, could be due to the distillation method and analysis conditions [27], or many extrinsic factors like temperature and rainfall [53], the geographic source of the species and the season of harvest [52,54], the stage of ripening, storage conditions of the sample (exposure to light, relative humidity, etc. ), and genetic and growth factors [53,55,56].…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…The available research data indicate that the biologically active potential of the various Artemisia species is far from being fully studied, and their conventional applications do not utilize their properties fully. Therefore, the current investigations [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] of the chemical compositions and biological activity of the various Artemisia L. species hold particular significance and are experiencing a real surge as they are presently in the focus of bioorganic and bioanalytical chemistry. The chromatography–mass spectrometry technique is widely acknowledged as the most-appropriate and -informative approach for the analysis of extracts or essential oils, specifically their chemical compositions, due to its ability to combine high separation power with reliable mass spectrometry detection [ 56 ].…”
Section: Introductionmentioning
confidence: 99%